Neuronal nicotinic receptors as analgesic targets: It's a winding road - Umana, Iboro C.; Daniele, Claire A.; McGehee, Daniel S. (Biochemical pharmacology, 2013)
Along with their well known role in nicotine addiction and autonomic physiology, neuronal nicotinic receptors (nAChRs) also have profound analgesic effects in animal models and humans. This is not a new idea, even in the early 1500s, soon after tobacco was introduced to the new world, its proponents listed pain relief among the beneficial properties of smoking. In recent years, analgesics that target specific nAChR subtypes have shown highly efficacious antinociceptive properties in acute and chronic pain models. To date, the side effects of these drugs have precluded their advancement to the clinic. This review summarizes the recent efforts to identify novel analgesics that target nAChRs, and outlines some of the key neural substrates that contribute to these physiological effects. There remain many unanswered mechanistic questions in this field, and there are still compelling reasons to explore neuronal nAChRs as targets for the relief of pain.